Treatment of large-scale mine drainage with high suspended solid and fluoride by the process of two-stage preprecipitation and mechanical clarifier: A case study of Zhengtong coal mine - GAO Jie (能源环境保护)
Treatment and resource utilization of mine drainage is an effective way to protect the ecological environment and address the issue of water shortage in mining areas. According to the characteristics of mine drainage of large water flow, high suspended solid, high salinity and containing fluoride, the purification process of two-stage preprecipitation and clarification was adopted in Zhengtong coal mine, and the mechanical clarification unit was optimized to synergistically remove suspended solid and fluoride. The operation result showed that the average SS removal rates of radial flow sedimentation tank, horizontal flow sedimentation tank and mechanical accelerated clarifier were 72. 5%, 48. 3% and 98.1%, respectively, under the conditions of the average concentration of influent SS was 3342 mg·L^-1 and the dosages of PAC 80 mg·L^-1 and PAM 0.8 mg·L^-1. The influent and effluent concentrations of fluoride were 1.20 mg·L^-1 and 0.93 mg·L^-1, respectively. The fluoride removal rate achieved 31.0%. The effluent quality indexes were better than the design criteria. The operation cost of mine drainage treatment was 0.34 yuan·ton^-1.